Transformasi Hukum Pembiayaan Kesehatan di Era Digital : Tantangan dan Peluang Kebijakan Kesehatan - Harianto Harianto; Marice Simarmata (International Forum of Researchers and Lecturers, 2025)
The existence of laws in health has been proven to have serious impacts on the health sector in various countries, including Indonesia. Through an analysis of philosophical texts and related research, this article reveals how corrupt practices affect the allocation of funds for the health system, disrupt the provision of adequate health facilities and services, and affect the quality of medical services. The economic implications of corruption on the health sector, including the high cost of obtaining quality health services and unequal access to health services. The social impacts of corruption are also analyzed, including poverty, unequal income distribution, and increased risk of criminal acts. In an effort to minimize the negative impacts of corruption on public health, this article proposes the implementation of strategies of transparency, accountability, and public participation. Implementation of the systeme-governmentand the active role of society ascitizen controlis a concrete step that can be taken to combat corruption and ensure more efficient and transparent use of public resources. The need for a joint role from the government, civil society, and the private sector in building a health system that is fairer, more transparent, and free from corruption. By strengthening the foundations of democracy and prioritizing transparency, Indonesia can move towards more equitable and quality public health for all people.